Aluminum alloy AA2024 coated with ZrO2 using a sol-gel-assisted dip-coating technique and its corrosion performance - Ganapathy, Veanuga; Kurniawan, Tedi; Mas Ayu, Hassan; Asmara, Y. P.; R., Daud; Prastomo, Niki; Dani Nandiyanto, Asep Bayu (Taylor's University, 2018)
Aluminum alloys has been widely used in most of engineering applications, such as marine industries and aerospace, due to its light weight and durability properties. In the aggressive environment, aluminum alloy becomes chemically reactive and losses its corrosion resistance that can significantly limit to its applications. One of the approaches that have been studied in this research is to improve the corrosion resistance of aluminum alloy by adding zirconium oxide (ZrO2) film coating. In the experimental procedure, aluminum alloy was dipcoated into the solution containing zirconium butoxide (as a precursor) in a specific solvent (consisting of acetone, ethanol, and nitric acid). Dipping process was conducted at different dipping-numbers, which are 3, 5, and 7 dipping number. After dip-coating process, the coated aluminum was annealed at 350°C for 3 hours. X-ray diffraction analysis confirmed that the coating film consists of tetragonal ZrO2. Then, increases in dipping number improved the surface quality of the coating layer, where number of cracks and black spots reduced continuously with higher dipping number. This condition gave positive impacts on the corrosion performance of the aluminum, where higher dipping number brings better corrosion protection in NaCl solution.